METHODOLOGY FOR ORGANIZING AND TEACHING POTTERY CIRCLES - Botirov Muxammadjon Abduqodirovich; Botirova Maftuna Muxammadjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article will focus on the role and practical significance of the application of new pedagogical technologies in the training “working out the drawing of the head of the Hudson with anatomical plaster”.